Sustainable maintenance strategies for government office buildings in emerging economies - Dithebe, Khotso; Aigbavboa, Clinton Ohis; Thwala, Wellington Didibhuku; Naik, Bhaven (Emerald Publishing Limited, 2025)
Provision of infrastructure development continues to be a great concern in emerging economies, particularly in ensuring sustainable growth through business continuity, and human development. The functionality and reliability of existing infrastructure is nowhere close to the aspirations of the global infrastructure initiative, thus affecting the rate at which services can be delivered to the public. Lack of understanding on the requirements of maintenance management has exacerbated the reliability of this infrastructure, particularly public office buildings. The expertly curated chapters provide an unambiguous perspective on the practice requirements of maintenance management for public office buildings. Perspectives shared in the book include but not limited to maintenance principles and practice specifications for public asset management. Facility management is mostly to benefit from the perspectives deliberated in the book. More so, government institutions and regulatory bodies will also benefit from the findings of the book regarding practice requirements of maintenance management for public office buildings. The book further contributes towards expanding the existing body of knowledge in the field of maintenance management for public buildings.